Pengaruh Brand Image dan Online Customer Review Terhadap Niat Membeli Kembali pada Produk Pinkflash di Shopee - Andira Velia Nastarina; Tri Yulistyawati Evelina (INDO PUBLISHING, 2026)
This study aims to analyze the influence of brand image and online customer reviews on the intention to repurchase Pinkflash products on Shopee, both partially and simultaneously. The study population consists of all followers of the Pinkflash Indonesia Official Shop on Shopee, totaling approximately 3.7 million accounts, with a sample of 100 respondents selected using purposive sampling. The study employed a quantitative approach, with data collected via a questionnaire and analyzed using multiple linear regression with IBM SPSS Statistics version The results indicate that both Brand image and Online customer reviews have a positive and significant effect, both individually and collectively, on the Repurchase intention for Pinkflash products on Shopee. The Online customer review variable had the most dominant influence on Repurchase intention. The coefficient of determination (R-squared) value of 0.665 indicates that 66.5% of the variation in Repurchase intention can be explained by these two variables, while the remainder is influenced by other factors outside the scope of this study. Future research is recommended to include additional variables, such as consumer trust, consumer satisfaction, product quality, or price, to gain a more comprehensive understanding of the factors influencing Repurchase intention.